Pengaruh Variasi Suhu Perawatan Beton Terhadap Nilai Kuat Tekan Beton Mutu K-350 - Setyawati, Desy Rahayu; Syahrul, Syahrul; Adi, Ari Sasmoko (Department of Architecture, Faculty of Engineering, 2023)
Concrete is a mixture of Portland cement or other hydraulic cement, fine aggregate, coarse aggregate, and water, with or without additives, forming a solid mass (SNI 03-2834-1993). The components of concrete consist of a mixture of fine and coarse aggregates with water and cement as the binder. Curing is performed after the concrete reaches its final setting, meaning the concrete has hardened, to ensure that the subsequent hydration process is not disrupted. The curing process is carried out for at least 7 (seven) days, or for concrete with high early strength, a minimum of 3 (three) days, and the concrete must be maintained in a moist condition unless accelerated curing methods are used (PB1989:29). This study was conducted to determine the effect of several methods, including immersion, non-immersion, and indoor curing, on the compressive strength of concrete. The results of the concrete compressive strength tests showed that indoor curing nearly met the quality requirement of K-350 concrete, while outdoor curing and immersion did not meet the K-350 concrete quality standard.